ANALISIS YURIDIS TERHADAP PENGARUH ABOLISI DALAM PENERAPAN HUKUM PADA KASUS KORUPSI TOM LEMBONG - Weni Fina Indah Qur’aini (Jurnal Jendela Hukum, 2026)
The granting of abolisi to Tom Lembong while the corruption case involving him was still under trial sparked controversy because it was deemed contrary to the principles of justice and legal certainty. The purpose of this study is to analyze how the amnesty affected the application of the law in corruption cases and its impact on the sense of justice, legal certainty, and public trust. The method used was a normative juridical method. The results indicate that halting the legal process through amnesty creates the impression that political power can influence law enforcement. The impact is seen in a weakened deterrent effect, the potential for political impunity, and a decline in public trust in law enforcement institutions. These results suggest that although amnesty falls within the President's constitutional authority, its use in corruption cases requires strict restrictions to avoid undermining anti-corruption efforts and maintaining a sense of justice in society.